2022
DOI: 10.3389/fsurg.2022.915599
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the systemic immune inflammation index in patients with metastatic and unresectable pancreatic cancer

Abstract: PurposeSystemic inflammatory markers may be predictors of the survival rate of patients with pancreatic cancer (PC). The aim of this work was to investigate the prognostic value of markers, mainly the systemic immune inflammation index (SII), in patients with metastatic and unresectable PC and to explore the relationship between markers and liver metastasis.MethodsRecords of patients with metastatic and unresectable PC at the Affiliated Hospital of Qingdao University from January 2000 to December 2019 and who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Patients with a high level of the inflammatory markers SII, neutrophil-to-lymphocyte count neutrophil/lymphocyte ratio (NLR), and the platelet-to-lymphocyte count, may be more prone to early liver metastasis. [16] Of note, findings of the present study conform with these previous information on the impact of SII with the severity of inflammation in the pancreatic tissue.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with a high level of the inflammatory markers SII, neutrophil-to-lymphocyte count neutrophil/lymphocyte ratio (NLR), and the platelet-to-lymphocyte count, may be more prone to early liver metastasis. [16] Of note, findings of the present study conform with these previous information on the impact of SII with the severity of inflammation in the pancreatic tissue.…”
Section: Discussionsupporting
confidence: 92%
“…In patients with metastatic or unresectable colon cancer, the higher the SII index, the shorter the survival period. And a high SII index may predict that liver metastases from colon cancer can occur at an early stage [ 20 ]. A meta-analysis included 3565 patients with esophageal cancer patients receiving operation in nine studies indicated that higher SII was associated with a shorter length of survival [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient age, clinical performance, nutrition, and hematological status play significant roles in determining their outcomes [3,4]. Systemic inflammation associated with cancer is a well-known factor that affects patient prognosis for different types of cancer [5][6][7].…”
Section: Introductionmentioning
confidence: 99%